Discharge timeliness and its impact on hospital crowding and emergency department flow performance. (4th February 2016) - Khanna, Sankalp; Sier, David; Boyle, Justin; Zeitz, Kathryn
Abstract: Objective: The objective of this research is to identify optimal inpatient discharge time targets to help hospitals reduce crowding, improve patient flow through the ED and balance staff workload. Methods: Fifteen months of emergency and inpatient records from a large quaternary teaching hospital were used to reconstruct patient pathways from hospital presentation to discharge. Discrete event simulation was used to assess operationally realistic discharge scenarios on flow performance. Main output measures included National Emergency Access Target (NEAT) performance (an ED performance metric), time spent waiting for a bed, hospital length of stay (LOS) and occupancy. Results: Similar levels of improvement in NEAT performance (16%), and reductions in average bed occupancy (1.5%) and inpatient bed wait time (25%) were observed across the simulation that discharged 80% patients before 11 a.m. and one that spread the target between 10 a.m. and 2 p.m. Individual inpatient wards returned potential improvements in NEAT performance (median 10%, interquartile range (IQR) 7%), and reductions in hospital LOS (median 1%, IQR 1%) and average occupancy (median 1%, IQR 2%) across the discharge scenarios. Conclusions: Conventional discharge targets like '80% by 11 a.m.' and others that spread targets across the day to balance staff workload freed up the equivalent of nine available beds for incoming patient flow, significantly reducing time spent waiting for an inpatient bed, hospital LOS and occupancy, and delivering much needed improvements in NEAT performance. While different strategies and workload distributions may suit individual hospital services, the study makes a strong case for improving 'early in the day' discharge timeliness to deliver better ED flow.